Cell-based approach for 3D reconstruction of lymphatic capillaries in vitro reveals distinct functions of HGF and VEGF-C in lymphangiogenesis. (February 2016) - Gibot, Laure; Galbraith, Todd; Kloos, Bryan; Das, Suvendu; Lacroix, Dan A.; Auger, François A.; Skobe, Mihaela
Abstract: Regeneration of lymphatic vessels is important for treatment of various disorders of lymphatic system and for restoration of lymphatic function after surgery. We have developed a method for generating a human 3D lymphatic vascular construct. In this system, human lymphatic endothelial cells, co-cultured with fibroblasts, spontaneously organized into a stable 3D lymphatic capillary network without the use of any exogenous factors. In vitro -generated lymphatic capillaries exhibited the major molecular and ultra-structural features of native, human lymphatic microvasculature: branches in the three dimensions, wide lumen, blind ends, overlapping borders, adherens and tight junctions, anchoring filaments, lack of mural cells, and poorly developed basement membrane. Furthermore, we show that fibroblast-derived VEGF-C and HGF cooperate in the formation of lymphatic vasculature by activating ERK1/2 signaling, and demonstrate distinct functions of HGF/c-Met and VEGF-C/VEGFR-3 in lymphangiogenesis. This lymphatic vascular construct is expected to facilitate studies of lymphangiogenesis in vitro and it holds promise as a strategy for regeneration of lymphatic vessels and treatment of lymphatic disorders in various conditions.